Enhancing PR Agenda Setting: KOL and Artificial Intelligence for Sustainable Development - Samantha Claudya; Angela Conie Marlynda; Carolina Saktya Pratista (Journal of Communication and Public Relations, 2025)
This research explores the strategic integration of Artificial Intelligence (AI) and Key Opinion Leaders (KOLs) within Public Relation (PR) campaigns aimed at advancing the Sustainable Development Goals (SDGs). Utilizing Agenda Setting Theory, the study examines how AI enhance the precision of sustainability objectives. Data gathered through a mixed-methods approach, involving in-depth interviews with PR practitioners and quantitative surveys, to assess the adoption and efficacy of AI in managing KOL partnerships. Key findings indicate that 45.5% of respondents use AI to optimize KOL interactions, while 33.3% incorporate KOLs into campaigns focused on SDG-related initiatives. Furthermore, 44.4% of respondents emphasize the critical importance of credibility in determining the success of KOL-driven campaigns. However, challenges remain, as 22.2% of professionals report difficulties in AI adoption, citing a lack of technical training as a barrier. The study concludes that AI significantly enhances PR strategies by improving audience targeting and campaign management, though human expertise remains essential in ensuring ethical decision-making and contextual relevance, particularly in culturally diverse regions such as Indonesia. The findings contribute to the growing body of knowledge on the intersection of AI, PR, and sustainability, providing practical recommendations for future campaigns aimed at promoting global development goals. To enhance the relevance of the study within the field of public relations and sustainability, keywords such as Agenda Setting Theory have been incorporated to better align the paper’s focus with strategic communication frameworks.